Researching tourism, leisure and hospitality for dissertations and theses - Mason, Peter
"Writing a dissertation can be a daunting topic - Researching Tourism, Leisure and Hospitality for Dissertations and Theses 2nd ed is a unique text that takes away the stress, worry and confusion by providing a step-by-step, user friendly guide to all you need to know to successfully research and compile your dissertation or thesis. Now in its second edition, this bestselling text has been fully revised and updated, and now includes two new chapters looking at conducting mixed methods research, as well as analysing mixed methods research. Clearly links research processes with the presentation of these in the writing of dissertations and theses. Draws on the work of undergraduate, postgraduate and PhD students the author has supervised, over 30 years to provide examples of dissertation/theses material. Uses case studies/examples based on the authors own peer reviewed research. Written in an accessible style. Presents tried and tested student activities. It provides a discussion of research approaches, looking at key differences and similarities. A critical evaluation of these different approaches is provided and, importantly, a discussion on selecting the appropriate approach(es) for your dissertation. It takes the reader from the initial idea and topics, through the literature review, methodology, presenting and analysing results and successfully making conclusions. Unlike other texts available, this book includes case studies based on the authors own research, as well as students work, to demonstrate different research approaches and techniques, providing an opportunity for criticism and a discussion on learning from mistakes. A must-have text for all students on how best to conduct research, compile your findings and to present them in the resulting dissertation." --